Communicating at work : - Adler, Ronald B (McGraw-Hill, 2010)
This book takes a pragmatic approach that features a strong multicultural focus, a heavy emphasis on effective presentations, and a pedagogical program designed to encourage group activities and skill building. This work provides coverage of new pedagogy, key new topics and an expansion of other important concepts including sources of on-the-job conflict, how to use informational interviews for career advancement, and stages in group problem-solving